Why Trades Get No Respect; Defending the Editorial Budget; What's Really Happening in the Job Market; Marketing is Everything; The Scientific Poster: Guidelines for Effective Visual Communication; Editing and Publication: A Training Manual - Kurt Knebusch; Ken Kingsley; Carol Sanders Reiner; K. Robert Kern (Journal of Applied Communications, 1991)
Reviews of "Why Trades Get No Respect," by Richard M.O'Connor; "Defending the Editorial Budget," by Frank Finn; "What's Really Happening in the Job Market," by Kathryn Kane; "Marketing is Everything," by Regis McKenna; "The Scientific Poster," by Diane L. Matthews; "Editing and Publication: A Training Manual," by Ian Montagnes.